Effect of gonadotropins and alpha 2u-globulin on testicular steroidogenesis and spermatogenesis in melatonin-treated rats - Biswas, R; Biswas, NM; Mandal, H; Biswas, NM (Journal of College of Medical Sciences-Nepal, 2012)
Administration of melatonin (400?g/100g bd.wt.) for 14 days caused a fall in weights of the testes and accessory sex organs and testicular 17?-hydroxysteroid dehydrogenase (17?-HSD) but rise in 3?-hydroxysteroid dehydrogenase (3?-HSD) activity, decreased spermatogenesis, serum level of gonadotropins, testosterone and alpha 2u-globulin, The animals treated with melatonin when received gonadotropins or alpha 2u-globulin for the last seven days reversed the weight of testis and accessory sex organs, 3?-HSD, 17?-HSD activities, serum level of gonadotropins, testosterone and alpha 2u-globulin when compared with melatonin-treated rats. It is concluded that alpha 2u-globulin prevents testicular degeneration in melatonin-treated rats by stimulating the synthesis of gonadotropins. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-1, 7-12 DOI: http://dx.doi.org/10.3126/jcmsn.v8i1.6819